Dietjourneybuddy: A-2 week weight loss monitoring & tracking mobile application / Nursara Salsabilla Mohd. Nizam - Mohd. Nizam, Nursara Salsabilla (2022)
This project developed a weight-loss journey with a monitoring and tracking mobile application called DietJourneyBuddy. The app helps people to monitor and manage user’s weight every day towards weight lost journey. The objective of this project is to identify the user’s requirements, to design and to develop the DietJourneyBuddy app. The features provided for the user in this mobile application including the monitoring and tracking mobile app. The app would track the user’s weight and the app monitor the user’s weight progress. This app also provided features for user to have change the target weight using default. Then, this application has limitations such as the app are only for single user and the app only covered the English version for the language of the app. The methodology used is Mobile Application Development Life Cycle (MADLC). It will be developed from the identification phase till the testing phase only. Testing is done using the system usability scale (SUS). In the future, this application can be used to monitor the eating behavior user take instead of monitoring their weight. This project primarily benefits the users who wants to lose their weight accordingly especially the members of gymnasium in UiTM Shah Alam who wants to lose their weight. Based on the user testing, all the functionalities in the mobile app functioning well when user anticipating in the app. According to the tester, the application is easy to use, look minimalist and the description to input something in the app was clear and user-friendly. The tester mentioned they satisfied with features to input and update the weight that was displayed in kilogram. For future recommendation, the sign-up would be much better by requesting user to input Gmail account so that the account can be recovered if user did not remember their password.